ASSESSMENT OF EDUCATION AND INFORMATION GUIDANCE SERVICES IN CURBING SOCIAL VICES AMONG SECONDARY SCHOOLS STUDENTS IN DELTA STATE - JESUOROBO, WELLINGTON OMOSEFE; OTUONYE, MARY ANGELA IJEOMA (Sokoto Educational Review, 2022)
This study assessed the provision of education and information guidance services by school counsellors in curbing social vices among secondary school students in Delta state. It specifically found out the extent to which education and information guidance services are provided by school counsellors to senior secondary school students in the Sapele Local Government Area of Delta state. A descriptive research design was adopted for the study. Two research questions were formulated to guide and direct the study. The sample consisted of 300 Senior Secondary (SS) 2 students selected from three senior secondary schools in Sapele, through a simple random sampling method. A 25-item questionnaire entitled "Education and Information Guidance services Questionnaire (EIGSQ)" constructed by the researchers was used for data collection. Two test experts validated the instrument. Cronbach Alpha Reliability formula was used to calculate the reliability coefficient of the instrument and a reliability index of 0.81 was obtained. Mean and Standard Deviation scores were used to answer the research questions. The findings revealed that the majority of the students have not been receiving education and information guidance services even though they have professional counsellors in the schools. The reason is that the school counsellors are saddled with teaching subjects and other administrative duties. Based on the findings, it was recommended that guidance and counselling should be included in the school timetable, and counsellors should step up in their counselling roles to ensure the students’ counselling needs are met.